Violence against adolescents during the COVID-19 pandemic in Bandung, Indonesia - Nita Arisanti; Putri Sartika Dewi; Nia Kania; Meita Dhamayanti (Paediatrica Indonesiana, 2023)
Background Violence against children includes all forms of violence against people under 18 years old, whether perpetrated by parents or other caregivers, peers, romantic partners, or strangers. During the COVID-19 pandemic, strained parent-child relationships due to family financial pressure, physical or mental health problems, and lockdown conditions that kept families at home and in close proximity for long periods of time might have exacerbated any underlying tensions. Objective To describe violence against adolescents in Bandung during the COVID-19 pandemic, in the form of psychological violence, physical violence, neglect, and sexual abuse. Methods This descriptive study was held from October to December 2020. Subjects were adolescents aged 12-18 years attending junior and senior high school in Bandung. Subjects filled the International Society for Prevention of Child Abuse and Neglect (ISPCAN) Child Abuse Screening Tool-for Children (ICAST-C) questionnaire (Indonesian version). Results The most common forms of violence experienced by adolescents in Bandung during the COVID-19 pandemic were being ignored (psychological violence), startled aggressively (physical violence), and being made to feel unimportant (neglect). Sexual abuse was reported by a minority of subjects. Conclusion The predominant type of violence against adolescents in Bandung during the COVID-19 pandemic was psychological violence, followed by physical violence and neglect.